The Use of Python in AI and Its Impact on Inventory Management in America 2023 - Medina Condori, Vanessa Natalia; Mendoza Ibarra, Veronica; Rondón Rojas, Abib Yehoshua Freddy; Salazar Quispe, Isabel Ciclari; Rojas Poma, Heidy Elizabteh; Aguilar Calderón, Henry Armando; Larios Soldevilla, Omar Alexis (LACCEI, 2024)
In the competitive market, companies face significant challenges in inventory management due to increasing demand. The implementation of advanced technological tools, such as Python with Artificial Intelligence (AI), offers an innovative solution to optimize these processes. Python, with its ability to automate tasks and manage large volumes of data through specialized libraries, enhances accuracy and efficiency in inventory management. This article focuses on the General Objective (GO) of determining the influence of Python with AI on inventory management in America during 2023. Additionally, Specific Objective 1 (SO1) seeks to ascertain how automation with Python AI influences inventory management, while Specific Objective 2 (SO2) evaluates the impact of using libraries with Python AI in this area. A systematic review of various information sources, including articles, theses, and reports from different databases, primarily in America, was conducted. The results indicate that the integration of Python with technologies such as AI has significantly reduced inventory control times and improved the accuracy of business operations. It is concluded that disseminating this information is crucial to highlight the benefits of implementing Python, as it can encourage the adoption of emerging technologies by more companies. This not only enhances their operational efficiency but also enables them to remain competitive in an ever-evolving market.